Experimental and theoretical modeling of the effects of pressure and secondary reactions on pyrolysis of JP-10 at supercritical pressures. (15th December 2021) - Wang, Yusen; Cheng, Yuxiang; Li, Minghao; Jiang, Pei-Xue; Zhu, Yinhai
Highlights: Effects of secondary reactions and pressure on pyrolysis of JP-10 are investigated. The formation of gas products is suppressed by increasing the pressure. Gas and liquid products are categorized as two and six types, respectively. A differential global reaction (DGR) model for JP-10 predicts pyrolysis accurately. An increase in pressure increases residence time and chemical heatsink. Abstract: Regenerative cooling is widely employed for thermal protection of hypersonic vehicles. Hydrocarbon fuels undergo pyrolysis in regenerative cooling channels at supercritical pressures, which affects the performance of regenerative cooling. Pressure and secondary reactions are the key factors that influence pyrolysis. Pyrolysis experiments of JP-10 (exo-tetrahydrodicyclopentadiene) were performed in an electrically heated vertical tube in the pressure range of 3.5–7 MPa and the conversion range of 0%–45%. The formation of gas products was suppressed by increasing the pressure. The effects of pressure and secondary reactions were significant on the distribution of some of the main products, such as ethylene and 1, 3-cyclopentadiene, but not for products such as propylene. A method for categorizing gas and liquid products was proposed. The gas and liquid products of JP-10 could be divided into two and six categories, respectively. Based on the differential global reaction modeling approach, a one-step reaction model for the pyrolysis of JP-10 at supercritical pressures was proposed, in which the stoichiometric coefficients were expressed as binary functions of pressure and fuel conversion to reflect the coupling effects of pressure and secondary reactions. The proposed model was implemented in one-dimensional theoretical model and a computational fluid dynamics model to predict JP-10 pyrolysis coupled with flow and heat transfer. The results demonstrated that the model accurately predicts the effects of both pressure and secondary reactions on pyrolysis. The results also showed that an increase in pressure increases the residence time at a fixed mass flow rate, which promotes fuel conversion and chemical heat sink.